Investigating the perceptions of preservice teachers on collaborative in-situ microteaching - Emrah Özcan; H. Gülru Yüksel (Universitas Ahmad Dahlan, 2022)
Micro-teaching has been criticized for its artificial nature, limited practice period, and inadequate feedback. Giving preservice teachers in-situ opportunities that they can collaborate on lesson planning, teach, and receive peer feedback can assist in addressing these drawbacks. To that end, an intervention study was devised to provide in-situ microteaching for preservice English teachers (PT). Following the intervention, we solicited PTs' feedback on the impact of the collaborative in-situ microteaching experience on their pedagogical knowledge development. A total of 41 PTs participated in the 14-week intervention program offered as part of the Teaching English to Young Learners (TEYL) course. Both quantitative and qualitative data were collected during this intervention study. A survey created by the researchers was used to gather quantitative data, and the reflection papers submitted by the participating PTs served as a source of qualitative data. The results revealed that participants rated the experience as having a moderate overall contribution to their pedagogical knowledge development. Collaborative in-situ microteaching (CiM) had a slightly higher influence on student teachers’ lesson delivery skills than on their lesson planning skills. As per the qualitative data, the most frequently mentioned benefits were acquiring expertise in classroom management, material development and lesson planning, and getting to know young learners.